2020
DOI: 10.21203/rs.2.23243/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibacterial Activities of Essential Oil and Fractions of Ethanolic extract of Echinops kebericho Tuber

Abstract: Background: Echinops kebericho is an endemic medicinal plant in Ethiopia traditionally used for treatment of various infectious diseases through different routes of administration such as inhalation, orally chewed, and topically sprayed to affected area. This study investigated antibacterial activity of the essential oil (EO) and the different fractions of ethanolic extract of Echinops kebericho tuber.Results: MIC of EO ranged from 78.125 µg/ml – 625 µg/ml and it was most active against methicillin resistant S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The fresh plant material was bought from Segno Gebeya, Dessie City Administration, about 400 km away from Addis Ababa, during the month of September 2021. The producer reported by Deyno et al 25 and Wondiafrash 26 were applied. The specimen was submitted to Addis Ababa University (AAU) National Herbarium of Ethiopia for identification and deposition voucher number.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fresh plant material was bought from Segno Gebeya, Dessie City Administration, about 400 km away from Addis Ababa, during the month of September 2021. The producer reported by Deyno et al 25 and Wondiafrash 26 were applied. The specimen was submitted to Addis Ababa University (AAU) National Herbarium of Ethiopia for identification and deposition voucher number.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained from the present study is comparable with reported data regarding the activity of crude extracts. 25 The synergic effect of phytochemicals as shown in Table 2 makes all the extracts promising and potent antibacterial agent compared with the standard chloramphenicol. In this study, the pure isolated compound DHCL showed higher activity than all the extracts as well standard.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…(14) The literature has shown that the addition of turmeric, cinnamon, and okra to the diet have positive effects on variables including body mass, blood glucose, lipid profile, and the immune system, such as increased production of immunoglobulin A (IgA). (15)(16)(17) Serum IgA was first discovered in 1953 (18) and mediates a variety of protective functions through interaction..with..FcRα..receptors..on..monocytes Ruzon-Camargo, F. I. et al…”
Section: Introductionmentioning
confidence: 99%
“…Serum IgA may also play a role in controlling the immune system through its binding to proteins that inhibit neutrophil chemotaxis (e.g., α-1-antitrypsin). (19) As mentioned above, studies that assess the action of turmeric, cinnamon, and okra are generally carried out in animals with some type of disease, such as overweight and diabetes, (16) or submitted to a diet rich in fructose, or with hyperlipidemia. (6,20) However, few studies have evaluated the effects of these plants on physiological parameters in healthy animals.…”
Section: Introductionmentioning
confidence: 99%
“…Part of this manuscript has been released as a pre-print at Researchsquare ( Deyno et al, 2020b ). We would like to thank Pharm-biotechnology and Traditional Medicine Center of Excellence (PHARMBIOTRAC) World Bank African center of excellence II (ACE-II) project for funding the research.…”
mentioning
confidence: 99%